Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.

Synthesis of gold, silver and their alloy nanoparticles using bovine serum albumin as foaming and stabilizing agent - Singh, A. V.; Bandgar, B. M.; Kasture, Manasi; Bhagavatula L. V. Prasad; Sastry, M. (Journal of Materials Chemistry, 2005)
A simple and convenient method for the synthesis of gold, silver and their alloy nanoparticles in a foam matrix using the protein bovine serum albumin (BSA) is reported. BSA is an excellent foaming agent and, by virtue of its zwitterionic character at the protein isoelectric point, may be used to bind to either cationic silver (Ag+) or anionic gold (AuCl4-) ions in the foam. The metal ions in the foam are thereafter reduced in situ to yield silver and gold nanoparticles. The versatility of an amphoteric foaming agent is further demonstrated by the simultaneous binding of Ag+ and AuCl4- ions with zwitterionic BSA leading to the possibility of obtaining Au-Ag alloy nanoparticles in the foam. The BSA molecules coat and stabilize the nanoparticles thus prepared eliminating the necessity of employing an additional stabilizing agent in the experimental recipe.

Static and dynamic magnetic properties of Co nanoparticles - Srinath, S.; Poddar, P.; Sidhaye, Deepti S.; Bhagavatula L. V. Prasad; Gass, James; Srikanth, H. (Journal of Nanoscience and Nanotechnology, 2008)
Co nanoparticles have been synthesized using wet-chemical methods. As-synthesized particles show a sharp low temperature peak in zero-field cooled (ZFC) magnetization well below the blocking transition temperature and this feature is associated with surface spin disorder. We have investigated the dynamic magnetic properties of Co using ac susceptibility and resonant RF transverse susceptibility (TS). We also studied the memory and relaxation effects in these nanoparticle systems. From these measurements we show a typical blocking behavior of an assembly of superparamagnetic nanoparticles with a wide distribution of blocking temperatures. The transverse susceptibility measurements on these particles show the presence of anisotropy even above the blocking temperature. The role of surface anisotropy and the size distribution of the particles on the observed memory and magnetic relaxation effects are discussed.
International Conference on Advanced Nano-Materials, Indian Inst Technol, Phys Dept, Bombay, INDIA, JAN 08-10, 2007
Keywords: Ac Susceptibility; Co Nanoparticles; Magnetic relaxation; Transverse Susceptibility

Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams

Synthesis of hydroxy-functional PMMA macromonomers by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
Living anionic polymerization has been utilized to synthesize hydroxy end-functionalized PMMA macromonomers with styryl or allyl functionalities as the polymerizable end-groups. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been terminated using 4-vinylbenzyl chloride (4-VBC) or allyl methacrylate (ALMA) to form -hydroxy–styryl and -hydroxy–allyl PMMA, respectively. These protected hydroxy-functionalized PMMA macromonomers have been characterized by GPC and 1H-NMR. Termination using 4-VBC led to 50% functionalization, whereas that using allyl methacrylate led to 100% functionalization of the hydroxy-PMMA.
Keywords: Anionic polymerization; functionalized initiator; Macromonomer

Synthesis and characterization of poly-L-lysine-grafted silica nanoparticles synthesized via NCA polymerization and click chemistry - Kar, Mrityunjov; Vijayakumar, P. S.; Bhagavatula L. V. Prasad; Sen Gupta, Sayam (Langmuir, 2010)
Polypeptide polymer-grafted silica nanoparticles are of considerable interest because the ordered secondary structure of the polypeptide grafts imparts novel functional properties onto the nanoparticle composite. The synthesis of poly-L-lysine-grafted nanoparticles would be of particular interest because the high density of cationic charges on the surface could lead to many applications such as gene delivery and antimicrobial agents. In this work, we have developed a ``grafting-to'' approach using a combination of NCA polymerization and ``click chemistry'' to synthesize poly-L-lysine-grafted silica nanoparticles with a high graft density of 1 chain/nm(2). The covalent attachment of poly-L-lysine to silica nanoparticles (PLL-silica) was confirmed using a variety of techniques such as C-13 CP MAS NMR, TGA, and IR. This methodology was then extended to graft poly-L-lysine-b-poly-L-leucine copolymer (PLL-b-PLLeu-silica) and poly-L-benzylglutamate (PLUG silica) onto silica nanoparticles. All of these polypeptide-grafted nanoparticles show interesting aggregation properties in solution. The efficacy of PLL-silica and PLL-h-PLLeu-silica as antimicrobial agents was tested on both gram-negative B. cull and grain-positive Bacillus subtilis.

Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.

Segmented flow synthesis of Ag nanoparticles in spiral microreactor: role of continuous and disperzsed phase - Kumar, D. V. Ravi; Bhagavatula L. V. Prasad; Kulkarni, Amol A. (Chemical Engineering Journal, 2012)
This work focuses on understanding the effect of segmented flow on the nanoparticle size distribution in a unidirectionally expanding spiral microreactor, where secondary flows are prevalent in the absence of segmentation. Stearic acid sophorolipid reduced/capped Ag NPs were synthesized in the aqueous phase and air or kerosene was used as inert phases for creating the gas-liquid and liquid-liquid segmented flow, respectively. While, in one case the reactant phase is in the form of dispersed phase slugs, in the other case it is in the form of continuous phase, each exhibiting a different behavior. The slug sizes and the slip velocity, both of which govern the nature of internal mixing in the reactant phase slug controlled the nanoparticle size distribution. This observation was consistent for both, gas-liquid and liquid-liquid segmented flows. The micromixer having smaller orifice diameter yielded smaller slugs and also a narrow particle size distribution. In general, the particle sizes were much smaller for gas-liquid flow rather than for liquid-liquid flow. Because of the unidirectionally expanding spiral geometry of the channel, at any given condition, unsteady behavior of slugs due to continuously varying radius of curvature results in variation in the slip velocity along the length of microchannel. This effect was seen to further narrow the particle size distribution than alone by the segmented flow. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Ag nanoparticles; Segmented flow synthesis; Sophorolipid; Spiral microreactor

Surfactant-free synthesis of anisotropic gold nanostructures: can dicarboxylic acids alone act as shape directing agents? - Kumar, D. V. Ravi; Kumavat, S. R.; Chamundeswari, V. N.; Patra, Partha Pratim; Kulkarni, A. A.; Bhagavatula L. V. Prasad (RSC Advances, 2013)
The present study describes the synthesis of gold nanostructures using different dicarboxylic (viz. oxalic, malonic, succinic, glutaric and adipic) acids as reducing agents in the absence of any other additives or surfactants. Various anisotropic structures such as kites, tadpoles, triangular/hexagonal plates, and twinned particles were seen to evolve depending on the molar ratio of dicarboxylic acid to HAuCl4 used. It was also demonstrated that gold nanostructure formation is hampered as the chain length/distance between two carboxylic acid groups increases. Among the various structures obtained the kite like structures displayed the largest surface enhanced Raman enhancement factors.

Synthesis of Ag-glyconanoparticles using C-glycosides, their lectin binding studies and antibacterial activity - Ramtenki, Vilas; Raju, D.; Mehta, Urmil J.; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2013)
Two 12-C-glycosyl dodecanoic acids, namely, 1-(alpha-D-mannopyranosyl)-12-dodecanoic acid and 1-(alpha-D-glucopyranosyl)-12-dodecanoic acid were synthesized. Their ability to act as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles is displayed. These Ag C-glycosyl nanoparticles were later utilized to investigate the carbohydrate-lectin interactions. Furthermore, the specificity of mannoside binding to the surface of the Gram negative bacterium Escherichia coli has been utilized to demonstrate the enhanced antibacterial activity of Ag-C-mannosyl nanoparticles towards this bacterium as compared to Ag-C-glycosyl nanoparticles.

Synthesis of triangular gold nanoplates: role of bromide ion and temperature - Kumar, D. V. Ravi; Kulkarni, Amol A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Synthesis of noble metal triangular nanoplates is a kinetically controlled process in which temperature and packing defects play a major role. Nucleation and growth process of kinetically controlled reaction can be greatly influenced by temperature affecting the yield and edge length of the triangles. Through a conventional batch mode process, here we study the effect of temperature on nucleation and growth of gold triangular nanoplates and obtain some insight of the temperature effects on the final yield and edge length of triangles. The role of Br- ions in the synthesis of triangular nanoplates is studied by varying the amount of CAB and by replacing the CTAB with HBr. The results show that, while CTAB controls the edge length and yield of triangles, its use is not mandatory to attain plate like morphology. Finally we show that, while the initial temperature of the reaction mixture governs the nucleation rate and the rate of temperature rise governs the growth rate of particles, they along with the concentration of Br- ions control the edge length and yield. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Halide ion effect; heat transfer; Kinetically controlled; Nature of gold precursor complex; Nucleation and growth; Optical properties

Synthesis and in situ observation of 3D super lattices of gold nanoparticles using oil-in-water emulsion - Dutta, Ankur; Chakraborty, Jayanta; Bhagavatula L. V. Prasad; Sahu, Puspanjali (Journal of Colloid and Interface Science, 2014)
In this work oil-in-water emulsion has been successfully used as a confined environment to grow 3D superlattices of gold nanoparticles. The superlattices were grown from 5 nm uniform gold nanoparticles using slow destabilization method. The confined environment was created by forming a stable emulsion where the gold colloid suspended in toluene was used as oil phase. Superlattices were also formed in bulk solution using the same slow destabilization method. A comparative study reveals that compact superlattices form more readily inside the emulsion drops as compared to bulk precipitation. The unstable colloid (in bulk or as emulsion) was aged for various periods at 5 degrees C to form more compact superlattices. The best superlattices with sharp corners are observed when the superlattices are formed inside the emulsion and aged for a month. Two key parameters, the incubation temperature and anti-solvent concentration, are optimized to obtain larger superlattices with sharp features. A new method is also demonstrated for in situ observation of superlattice formation using an optical microscope. 2014 Elsevier Inc. All rights reserved.
Keywords: 3D nanocrystal superlattices; In situ observation of superlattice formation; Monodisperse gold nanoparticles; Nanocrystal superlattices

Simple method for the preparation of ultra-small palladium nanoparticles and their utilization for the hydrogenation of terminal alkyne groups to alkanes - Seth, Jhumur; Kona, Chandrababu Naidu; Das, Shyamsundar; Bhagavatula L. V. Prasad (Nanoscale, 2015)
A simple and convenient method for the preparation of ultra-small palladium nanoparticles (Pd-NPs) by a modified digestive ripening method is described. These nanoparticles catalyse the hydrogenation of the terminal alkyne groups to alkanes selectively, and show no effect on other labile protecting and internal alkyne or internal/external alkene groups present in the molecule.

Self- assembly of isomannide-based monoesters of C18-fatty acids and their cellular uptake studies - Dhasaiyan, Prabhu; Parekh, Nimisha; Reddy, T. Vijai Kumar; Rani, G. Sandhya; Devi, B. L. A. Prabhavathi; Bhagavatula L. V. Prasad (RSC Advances, 2016)
The self-assembling behavior of oleic, elaidic and stearic acid-isomannide glycolipids is revealed. Amongst these, oleic and elaidic acid-based isomannide lipids self-assembled to form microspheres which were efficiently taken up by cancer cell lines enabling their usage for drug delivery applications.

Silver nanoparticles: a new perspective in endodontic therapy - Jadhav, Rajashree; Bhide, Shrinivas; Bhagavatula L. V. Prasad; Kunchiraman, Bipinraj; Shimpi, Jayesh; Nandhini, Usha (OAB Journal, 2016)
Silver has been in use in medicine since time immemorial because of its antimicrobial properties. But due to the emergence of antibiotics the use of silver has been declined. Several pathogenic bacteria have developed resistance against various antibiotics. This has led to reemergence of silver. Recently nano science and nanotechnology are gaining tremendous popularity. The small size of nanoparticles provides larger surface area and hence increases the effectiveness of nanoparticles. Silver nanoparticles are used in medical and dental applications ranging from silver based wound dressings, silver coated medicinal devices like catheters, endotrachial tubes, bone cements, in gels, lotions, cosmetics, in dental restorative materials, endodontic cements, dental implants caries inhibitory agents, and in prosthesis. The purpose of this article is to discuss briefly the potential role of silver nano particles in endodontic therapy.

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

Self - assemblies of bolaamphiphilic molecules - Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad (Chemical Record, 2017)
The current buzzword in science and technology is self-assembly and molecular self-assembly is one of the most prominent fields as far as research in chemical and biological sciences is concerned. Generally, self-assembly of molecules occurs through weak non-covalent interactions like hydrogen bonding, π–π stacking, hydrophobic effects, etc. Inspired by many natural systems consisting of self-assembled structures, scientists have been trying to understand their formation and mimic such processes in the laboratory to create functional “smart” materials, which respond to temperature, light, pH, electromagnetic field, mechanical stress, and/or chemical stimuli. These responses are usually manifested as remarkable changes from the molecular (e. g., conformational state, hierarchical order) to the macroscopic level (e. g., shape, surface properties). Many molecules such as peptides, viruses, and surfactants are known to self-assemble into different structures. Among them, glycolipids are the new entries in the area of molecules that are being investigated for their self-assembly characteristics. Among the different classes of glycolipids like rhamnolipids and trehalose lipids, owing to their biological preparations and their structural novelty, sophorolipids (SLs) are evoking greater interest among researchers. Sophorolipids are a class of asymmetric bolas bearing COOH groups at one end and sophorose (dimeric glucose linked by an unusual β(1→2) linkage). The extreme membrane stability of Archaea, attributed to the membrane-spanning bolas (tetraether glycolipids), has inspired chemists to unravel the molecular designs that underpin the self-assembly of bolaamphiphilic molecules. Apart from these self-assembled structures, bolaamphiphiles find applications in many fields such as drug delivery, membrane mimicking, siRNA therapies, etc. The first part of this Personal Account presents some possible self-assembled structures of bolaamphiphiles and their mechanism of formation. The later part covers our work on one of the typical bolaamphiphiles known as sophorolipids.
Keywords: Bolaamphiphiles; gels; self-assembly; sophorolipids; vesicles

Solvent-less solid state synthesis of dispersible metal and semiconducting metal sulfide nanocrystals - Bera, Abhijit; Busupalli, B.; Bhagavatula L. V. Prasad (ACS sustainable chem. eng, 2018)
Monolayer protected metal and metal sulfide nanocrystals (NCs) have mainly two constituents; the inorganic metal or metal chalcogenide complex as core and organic molecule as shell. Noticing that metal thiolates have these ingredients inbuilt in their structure, we investigated them as possible precursors for the preparation of monolayer protected metal and metal sulfide NCs via solid state grinding method. Accordingly silver and gold NCs have been prepared using a solvent less green approach, by the simple and convenient solid state grinding of the corresponding metal thiolate with sodium borohydride. Similarly, a large variety of uniform-sized semiconducting NCs of metal sulfides including PbS, CdS, ZnS, MnS, Ag2S, and CuS could also be synthesized by the same solid state route by grinding the metal thiolates with octyl dithiocarbamic acid (C8DTCA) and in some cases C8DTCA plus small amount of oleylamine as sulfur source. Interestingly, this simple technique could be used to prepare sub-3 nm NCs like Ag2S, PbS, and CuS which are otherwise difficult to prepare by the conventional high temperature solution routes also. Most gratifyingly, all these NCs, though were prepared by a solvent less grinding method, could be easily dispersed in nonpolar solvents as the preparation method ensued the formation of organic molecule capped NCs.